Federal Politics and Budget Deficits : Evidence from the States of India - Khemani, Stuti (World Bank, Washington, DC, 2014)
This paper tests two predictions implied by models of the common-pool game in federations where subnational governments are more likely to have higher deficits because they do not internalize the macroeconomic effects of fiscal profligacy. The first is that subnational governments that belong to the same political party as the central government have lower spending and deficits because they are more likely to be influenced to internalize the macroeconomic effects of additional local spending; and the second is that subnational governments that are more dependent on intergovernmental transfers have higher spending and deficits. We find that in 15 major states of India over the period 1972-1995, states in fact have substantially higher spending and deficits (higher by about 10 percent of the sample average) when their government belongs to the same party as that governing at the center; and that intergovernmental grants tend to have a counter-intuitive negative effect on spending and deficits. The additional deficit of affiliated states is financed almost entirely by additional loans from the central government (as opposed to the market) leading to our interpretation that similar political considerations influence the distribution of deficits across states as they do other intergovernmental grants. We argue that the evidence from India, contrasted with broader international evidence, indicates that the effect of fiscal institutions in a federation is sensitive to underlying political incentives. This underscores the overall importance of political institutions in determining the consolidated government deficit, relative to specific rules of intergovernmental transfers.